2006
DOI: 10.1007/s10295-006-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the microbial transformation of androst-1,4-dien-3,17-dione with Acremonium strictum

Abstract: The strain of Acremonium strictum PTCC 5282 was applied to investigate the biotransformation of androst-1,4-dien-3,17-dione (I; ADD). Microbial products obtained were purified by preparative TLC and the pure metabolites were characterized on the basis of their spectroscopic features (13C NMR, 1H NMR, FTIR, MS) and physical constants (melting points and optical rotations). The 15 alpha-Hydroxyandrost-1,4-dien-3,17-dione (II), 17 beta-hydroxyandrost-1,4-dien-3-one (III), androst-4-en-3,17-dione (IV; AD), 15 alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
(37 reference statements)
1
8
0
2
Order By: Relevance
“…13 C NMR signals are shown inTable 1. These data, in addition to the reported values(Faramarzi et al 2006;Al-Aboudi et al 2008), confirmed the proposed structure of androsta-1, 4-diene-3 17-dione.Androst-4-ene-3,17-dione (VI) Colorless crystals (crystallized from ethyl acetate); mp 176-178°C, [a] D ? 183°( CHCl 3 , c = 1.0), lit(Johnson et al 1960); mp 171.5-172.5°C, [a] D ?…”
supporting
confidence: 91%
See 1 more Smart Citation
“…13 C NMR signals are shown inTable 1. These data, in addition to the reported values(Faramarzi et al 2006;Al-Aboudi et al 2008), confirmed the proposed structure of androsta-1, 4-diene-3 17-dione.Androst-4-ene-3,17-dione (VI) Colorless crystals (crystallized from ethyl acetate); mp 176-178°C, [a] D ? 183°( CHCl 3 , c = 1.0), lit(Johnson et al 1960); mp 171.5-172.5°C, [a] D ?…”
supporting
confidence: 91%
“…117°(CHCl 3 , c = 1.0), lit (Faramarzi et al 2006 Table 1. The same NMR data were also reported earlier (Nagasawa et al 1969;Lin et al 2009).…”
Section: Biotransformation Products Of Cholesterol By G Neofelifaecismentioning
confidence: 99%
“…Reduction of 17-carbonyl group of ADD has been reported previously by Mucor racemosus and Acremonium strictum and Cephalosporium aphidicola fermention [11,12]. 11α-hydroxyandrost-1,4-diene-3,17-dione (III) which is used in the preparation of anti-osteoporosis active compounds, has been previously obtained by ADD biotransformation in Cephalosporium aphidicola, Rhizopus arrhizus and Aspergillus ochraceus culture media [13,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Androst-1,4-dien-3,7-dion (1), diperoleh berupa padatan putih dengan nilai [ ] 23 D +106,4 o (CHCl 3 ); literatur (Faramarzi, 2006)…”
Section: Metode Penelitianunclassified
“…Jenis senyawa steroid yang juga pernah diisolasi adalah β-sitosterol dan 3-β-hidroksi-21normetil-19-vinilidenilursan (Venkatesh et al, 2010) dari buah tumbuhan D. zibethinus. Senyawa 1 juga telah ditemukan dari beberapa tumbuhan seperti pada Scenedesmus quadricauda dan Acremonium strictum (DellaGreca, 1996;Faramarzi, 2006 (DellaGreca, 1996) c senyawa boldion dari Acremonium strictum (Faramarzi, M. A., 2006) 2) pada C 169,2 ppm (C-9"'), C 168,7 ppm (C-9), dan empat gugus metoksi pada C 56,7, 56,6, 56,5 dan 56,4 ppm. Berdasarkan data 1 H-NMR dan 13 C-NMR di atas dapat diketahui bahwa senyawa 2 adalah golongan lignan dengan nama boehmenan.…”
Section: Hasil Dan Pembahasanunclassified